'He's going to be a doctor in August': a narrative interview study of medical students' and their educators' experiences of aligned and misaligned assistantships. Issue 6 (10th June 2016) - Jones, Owen Meurig; Okeke, Chiemeka; Bullock, Alison; Wells, Stephanie E; Monrouxe, Lynn V
Abstract : Objective: To explore final-year students' and clinical supervisors' experiences of alignment and misalignment with future Foundation Year 1 (F1) posts in an assistantship programme in the UK. Setting: Assistantships are clinical placements in which students assist junior doctors by undertaking similar duties under supervision. Models of assistantship programmes vary across curricula. Some actively seek to align with students' initial postgraduate F1 post. To date, no research has examined the implications of this association for teaching and learning. Qualitative individual and group narrative interviews were conducted with students and supervisors of 2 Welsh medical schools to address: RQ1: How do students and supervisors understand the purpose of the longitudinal assistantship? RQ2: Does alignment/misalignment of the assistantship with students' initial F1 post influence students' and supervisors' teaching and learning experiences? Audio-recordings of interviews were transcribed, participants anonymised and framework analysis was used. Participants: A convenience sample of 4 participant groups comprised (1) final-year medical students whose assistantship and F1 post were aligned (n=27), (2) final-year medical students whose assistantship and F1 post were misaligned (n=18) and (3) supervisors (n=10, junior doctors; n=11, consultants). Results: All participant groups highlighted increased student confidence in undertaking the duties of an F1 doctor arising from their assistantship period. Learning transferable skills was also highlighted. Many students considered themselves to be team members, 'learning the trade' as they shadowed their F1. Opportunities for caring for acutely unwell patients were scarce. The evidence shows enhanced engagement for students aligned to their first F1 post with greater opportunities for workplace acclimatisation. Those who were misaligned were perceived as being disadvantaged. Conclusions: Our findings suggest that alignment with students' first F1 post enhances the assistantship experience. Further longitudinal assessment is required to examine whether and how this translates into improvements in functioning and reductions in stress and anxiety during this transitional period.